1999
DOI: 10.1128/aem.65.2.828-833.1999
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Factors Associated with Synthesis of the Osmolyte Glycine Betaine in the Halophilic Methanoarchaeon Methanohalophilus portucalensis

Abstract: The halophilic methanoarchaeon Methanohalophilus portucalensis can synthesize de novo and accumulate β-glutamine, N ɛ-acetyl-β-lysine, and glycine betaine (betaine) as compatible solutes (osmolytes) when grown at elevated salt concentrations. Both in vivo and in vitro betaine formation assays in this study confirmed previous nuclear magnetic resonance 13C-labelling studies showing that the de novo synthesis of betaine proceeded from glycine, sarcosine, and dimethylglycine to form betaine thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…More importantly, in vitro studies show that the methylation reactions are K ϩ dependent, with little betaine accumulating below 0.4 M K ϩ ; at this potassium concentration sarcosine was the major product. K ϩ concentrations above 0.4 M enhanced GB synthesis from sarcosine and N,N-dimethylglycine (37). This observation suggests that control of betaine synthesis is modulated by intracellular K ϩ ; this cation may also function as an intracellular signal for osmoregulation in M. portucalensis.…”
Section: Biosynthesis Of Osmolytesmentioning
confidence: 77%
See 1 more Smart Citation
“…More importantly, in vitro studies show that the methylation reactions are K ϩ dependent, with little betaine accumulating below 0.4 M K ϩ ; at this potassium concentration sarcosine was the major product. K ϩ concentrations above 0.4 M enhanced GB synthesis from sarcosine and N,N-dimethylglycine (37). This observation suggests that control of betaine synthesis is modulated by intracellular K ϩ ; this cation may also function as an intracellular signal for osmoregulation in M. portucalensis.…”
Section: Biosynthesis Of Osmolytesmentioning
confidence: 77%
“…Methanohalophilus portucalensis is relatively unique in the archaeal domain in that it can synthesize GB de novo (36). The biosynthesis of GB in this organism occurs by methylation of glycine (56) with S-adenosylmethionine as the methyl donor (37). More importantly, in vitro studies show that the methylation reactions are K ϩ dependent, with little betaine accumulating below 0.4 M K ϩ ; at this potassium concentration sarcosine was the major product.…”
Section: Biosynthesis Of Osmolytesmentioning
confidence: 99%
“…7 In this study, we observed the presence of GNMT in cholangiocytes, which are also responsible for digestive enzyme secretion. Previously, Lai et al 15 reported that GNMT plays a major role in osmoregulation in halophilic methanoarchaea, suggesting GNMT involvement in regulating the secretory function of cells. It is noteworthy that the GNMT expression pattern in cholangiocarcinoma tissues differs from that seen in normal bile ducts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on an amino acid, methylglycine (MeGly sarcosine), in Cucurbita maxima xylem sap collected from roots. MeGly has previously been detected in low amounts in plant tissues and is an intermediate in the synthesis of betaine [trimethylglycine (TMG)] which acts as an osmoprotectant (Chen and Murata 2002, Lai et al 1999, Withers and Guppy 1996. The presence of MeGly in xylem sap and the physiological effects of MeGly on plant growth and development have never been reported before.…”
Section: Introductionmentioning
confidence: 99%